Proliferation of Halal Regulation and Enforcement in Indonesia and Malaysia - Jalaluddin, Jalaluddin; Azhar, Alias; Muzainah, Gusti; Aseri, Muhsin; Al Amruzi, M. Fahmi (Journal of Human Rights, Culture and Legal System, 2024)
As part of safeguarding human rights, Indonesia has issued regulations on halal products that encourage entrepreneurs to certify their products. To facilitate this effort, the country has implemented several policies. Adopting a human rights perspective, this article aims to elucidate the government's policies on halal products at the regulatory and implementation levels. To attain a more comprehensive understanding, this research employs a legal comparative approach, using Malaysia as a benchmark. The findings of this study indicate that normatively, Indonesia has generated a range of legal instruments serving as the foundation for halal products. These legal instruments are systematically implemented, from the central government down to the grassroots level. However, this implementation encounters challenges such as normative ambiguity and the expansive interpretation of products that require halal certification. This is in contrast to Malaysia, which regulates halal products in a more dynamic and flexible manner.